Work Motivation and Work Discipline on The Performance of Grab Drivers in Palembang - Su’aidy Su’aidy (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2023)
The research objective was to examine the influence of work and work motivation disciplinary variable on the performance of Grab Palembang drivers. Population In this study, the number of Grab Palembang drivers cannot be known certainty. The number of samples used was 96 drivers and was determined using Slovin formula. The sampling technique uses accidental sampling. The data type is primary where the data collection method uses a questionnaire given to the driver faced. Data analysis techniques include multiple linear regression, t test, F test and coefficient of determination (R2). The result of data analysis shows that motivation and work discipline have a significant effect on the performance of Grab Palembang drivers, both partially and simultaneously. The coefficient of determination (R2) is 0.337 which means that the independent variables consist of work motivation and Work discipline affects the performance of Grab Palembang drivers by 33.7%. the remaining 66.3% is influenced by other variables.